2015
DOI: 10.1016/j.chemosphere.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and sublethal effects of six insecticides to last instar larvae and adults of the biocontrol agents Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) and Adalia bipunctata (L.) (Coleoptera: Coccinellidae)

Abstract: To further develop Integrated Pest Management (IPM) strategies against crop pests, it is important to evaluate the effects of insecticides on biological control agents. Therefore, we tested the toxicity and sublethal effects (fecundity and fertility) of flonicamid, flubendiamide, metaflumizone, spirotetramat, sulfoxaflor and deltamethrin on the natural enemies Chrysoperla carnea and Adalia bipunctata. The side effects of the active ingredients of the insecticides were evaluated with residual contact tests for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 34 publications
10
58
0
6
Order By: Relevance
“…The insecticide acetamiprid upon immatures and adults of the ectoparasitoid Aphytis melinus DeBach (Hymenoptera: Aphelinidae) did not affect the development of the immature stages of the natural enemy until pupation [67]. The toxicity and sublethal effects upon fecundity and fertility of six insecticides upon on the natural enemies Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) and Adalia bipunctata (Linnaeus) (Coleoptera: Chrysopidae) demonstrated that deltamethrin affected the reproduction parameters (fecundity and fertility) of C. carnea adults, while caused the total mortality of A. bipunctata larvae and adults [68]. The lethal and sublethal effects of lufenuron insecticide on Diatraea flavipennella (Box) (Lepidoptera: Crambidae) and its parasitoid Cotesia flavipes (Cameron) (Hymenoptera: Braconidae) were reported as a delay in the development period of C. flavipes when parasitizing D. flavipennella larvae that survived to sublethal exposure of the insecticide [69].…”
Section: Sublethal Effects Of Insecticides On Biological Controlmentioning
confidence: 99%
“…The insecticide acetamiprid upon immatures and adults of the ectoparasitoid Aphytis melinus DeBach (Hymenoptera: Aphelinidae) did not affect the development of the immature stages of the natural enemy until pupation [67]. The toxicity and sublethal effects upon fecundity and fertility of six insecticides upon on the natural enemies Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) and Adalia bipunctata (Linnaeus) (Coleoptera: Chrysopidae) demonstrated that deltamethrin affected the reproduction parameters (fecundity and fertility) of C. carnea adults, while caused the total mortality of A. bipunctata larvae and adults [68]. The lethal and sublethal effects of lufenuron insecticide on Diatraea flavipennella (Box) (Lepidoptera: Crambidae) and its parasitoid Cotesia flavipes (Cameron) (Hymenoptera: Braconidae) were reported as a delay in the development period of C. flavipes when parasitizing D. flavipennella larvae that survived to sublethal exposure of the insecticide [69].…”
Section: Sublethal Effects Of Insecticides On Biological Controlmentioning
confidence: 99%
“…In IPM programmes, identification of insecticides that are not harmful to biological control agents is a key concern for developing effective IPM strategies, because using biological control agents may not always be effective enough to control pest populations and thus insecticide treatments may be needed. (Stark et al 2007;Garzón et al 2015). Therefore, surveying the impact of pesticides on beneficial arthropods, chiefly in greenhouses, could be very important.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies regarding the effects of pesticides on beneficial species (Zhang & Sanderson 1990;Spollen & Isman 1996;Moscardini et al 2013;Garzón et al 2015;Nemec et al 2016). Most ones have focused on immediate and acute toxicity of pesticide but a few studies have demonstrated the relationship between pesticide residue and mortality of exposed beneficial arthropods (Bellows et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Basándonos en resultados de nuestro grupo, el sulfoxaflor puede ser definido como un insecticida poco selectivo al producir una alta mortalidad de los adultos de distintas especies de enemigos naturales como A. ervi, Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae), M. pygmaeus y O. laevigatus (100%, 56,67%, 74,33% y 100%, respectivamente), tras la exposición de los mismos a residuos frescos (Manzanares, 2012;Olivares, 2012;Guisado, 2014;Garzón et al, 2015a).…”
Section: Persistenciaunclassified